On the sharp constant for starlikeness - Chen Keying (International Journal of Mathematics and Mathematical Sciences)
We obtain a sharp constant of the sufficient condition for p-valently starlikeness, which had been studied by Nunokawa (1991), Obradović and Owa (1989), and Li (1993).